2018
DOI: 10.1016/j.envpol.2017.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lung cell toxicity of various gasoline engine exhausts using a versatile in vitro exposure system

Abstract: Adverse effect studies of gasoline exhaust are scarce, even though gasoline direct injection (GDI) vehicles can emit a high number of particles. The aim of this study was to conduct an in vitro hazard assessment of different GDI exhausts using two different cell culture models mimicking the human airway. In addition to gasoline particle filters (GPF), the effects of two lubrication oils with low and high ash content were assessed, since it is known that oils are important contributors to exhaust emissions. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…The exposure to complete gasoline exhaust from engines with and without particle filters and using various fuels for 6 h followed by a 6-h post-incubation period had no effect on oxidative stress and inflammation-related genes in a multicellular human lung model and in MucilAir TM . However, the repeated 3 × 6 h exposure to an exhaust from an engine without the filter, followed by post-incubation periods, increased the expression of HMOX1 and TNFα genes in the multicellular model suggesting that longer exposure is required to induce the biological effects [14]. The effect of ethanol-containing fuels was tested in the multi-cellular human lung model consisting of three cells types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exposure to complete gasoline exhaust from engines with and without particle filters and using various fuels for 6 h followed by a 6-h post-incubation period had no effect on oxidative stress and inflammation-related genes in a multicellular human lung model and in MucilAir TM . However, the repeated 3 × 6 h exposure to an exhaust from an engine without the filter, followed by post-incubation periods, increased the expression of HMOX1 and TNFα genes in the multicellular model suggesting that longer exposure is required to induce the biological effects [14]. The effect of ethanol-containing fuels was tested in the multi-cellular human lung model consisting of three cells types.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the endpoints to be assessed, in vitro toxicity tests of vehicle emissions may be carried out in various settings. They include for example the exposure of the test system to complete emissions [9,10,11,12,13,14], suspended particles [15,16,17,18], or to extracts from particles [19,20,21,22]. Each of these approaches has its specific advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown that exposure to primary PM emissions from mobile sources is linked directly to adverse health implications (Bisig et al, 2018;Tzamkiozis et al, 2010;Seagrave et al, 2002). Epidemiologic and toxicological studies have reported that elevated levels of PM are associated with cardiopulmonary mortality and morbidity (Araujo and Nel, 2009;Bates et al, 2015;Reed et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other ALI concepts (Phillips et al 2005;Savi et al 2008;Bisig et al 2018) choose different setups, for instance for minimum air velocity at the cell surface to mimic the situation in the alveolar space of the lungs more closely, thereby avoiding the cell stress from the radial shear flow in the stagnation point setup.…”
Section: Introductionmentioning
confidence: 99%